Clinicopathological and prognostic significance of preoperative serum epidermal growth factor levels in patients with oral squamous cell carcinoma. Issue 10 (October 2018) - Lin, J.-S.; Sun, F.-J.; Lin, P.-Y.; Chang, K.-W.; Yang, C.-C.; Liu, C.-J.
Abstract: Epidermal growth factor (EGF) promotes tumourigenesis and tissue repair of epithelial and mesenchymal cells and has a role in chemotaxis, mitogenesis, cell motility, and cytoprotection. It also enhances the growth of cancers. EGF may therefore have a role in the initiation or promotion of oral carcinogenesis. The cases of 152 patients with oral squamous cell carcinoma whose preoperative serum EGF level was determined by enzyme-linked immunosorbent assay were analyzed retrospectively, along with those of 40 age- and sex-matched controls. Patients with higher levels of EGF were more likely to have neck lymph node metastasis ( P  = 0.026), advanced stage cancer ( P  = 0.04), and a worse survival status ( P  = 0.0019). Multivariate analysis using the Cox proportional hazards model indicated that the EGF level was an independent predictor of poor survival (hazard ratio 1.99, P  = 0.018). Patients with higher preoperative serum EGF levels had significantly poorer cancer-specific survival by Kaplan–Meier analysis ( P  = 0.032). This study indicates that a higher preoperative serum EGF level is associated with neck lymph node metastasis, more advanced stage, and poor survival. EGF should be considered as a potential prognostic biomarker and a therapeutic target for patients with oral cancer.